2021
DOI: 10.7759/cureus.13886
|View full text |Cite
|
Sign up to set email alerts
|

Interspinous Process (ISP) Devices in Comparison to the Use of Traditional Posterior Spinal Instrumentation

Abstract: A systematic literature review was conducted on studies comparing interspinous process (ISP) devices to traditional methods of posterior spinal instrumentation (pedicle screw-rod construct), in terms of indications of use, complications, pain assessment, estimated blood loss, length of hospital stay, reoperation rates, and return to work. The objective was to analyze, evaluate and summarize the current published literature on the proposed efficacy and clinical and surgical long-term outcomes of the ISP device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Interspinous spacers (ISPs) have gained popularity as an alternative treatment for lumbar degenerative diseases, serving to decrease the intradiscal pressure (IDP) and maintain the intervertebral height [3]. Biomechanical studies have demonstrated that ISPs reduce hyperextension at the instrumented level, increase the dimensions of the neural foramen and spinal canal, and decrease the IDP [4]. However, the long-term clinical results of ISPs have not been satisfactory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interspinous spacers (ISPs) have gained popularity as an alternative treatment for lumbar degenerative diseases, serving to decrease the intradiscal pressure (IDP) and maintain the intervertebral height [3]. Biomechanical studies have demonstrated that ISPs reduce hyperextension at the instrumented level, increase the dimensions of the neural foramen and spinal canal, and decrease the IDP [4]. However, the long-term clinical results of ISPs have not been satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily attributed to the weak structural strength of the spinous process and the unstable fixation provided by ISPs. Complications such as a spinous process fracture, ISPs loosening, and the breakage of the fixation device often necessitate revision surgery [4][5][6]. Hence, there is a need for a new device that can effectively slow down the progression of lumbar degenerative diseases while minimizing complications, particularly in patients with osteoporosis.…”
Section: Introductionmentioning
confidence: 99%